1999
DOI: 10.1074/jbc.274.42.30115
|View full text |Cite
|
Sign up to set email alerts
|

Mammal-specific, ERK-dependent, Caldesmon Phosphorylation in Smooth Muscle

Abstract: Caldesmon is an actin-, tropomyosin-, myosin-, and calmodulin-binding protein that is alternatively spliced to yield either a 93-kDa protein (high molecular mass caldesmon (h-CaD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
58
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 26 publications
6
58
0
Order By: Relevance
“…In cultured smooth muscle cells where dedifferentiation renders expression switchover of many contractile proteins to the non-muscle isoforms, phosphorylation of l-CaD was also detected upon serum stimulation [41]. Such an increase in phosphorylation was markedly reduced by the MEK inhibitor PD98059, but not by the p38 MAPK inhibitor SB203580 [41]. These results strongly point to extracellular signal-regulated kinase (Erk)-induced phosphorylation of l-CaD during cell proliferation.…”
supporting
confidence: 47%
See 2 more Smart Citations
“…In cultured smooth muscle cells where dedifferentiation renders expression switchover of many contractile proteins to the non-muscle isoforms, phosphorylation of l-CaD was also detected upon serum stimulation [41]. Such an increase in phosphorylation was markedly reduced by the MEK inhibitor PD98059, but not by the p38 MAPK inhibitor SB203580 [41]. These results strongly point to extracellular signal-regulated kinase (Erk)-induced phosphorylation of l-CaD during cell proliferation.…”
supporting
confidence: 47%
“…The kinase responsible for the in vivo phosphorylation has been identified to be mitogen activated protein kinase (MAPK; see [39,40]). In cultured smooth muscle cells where dedifferentiation renders expression switchover of many contractile proteins to the non-muscle isoforms, phosphorylation of l-CaD was also detected upon serum stimulation [41]. Such an increase in phosphorylation was markedly reduced by the MEK inhibitor PD98059, but not by the p38 MAPK inhibitor SB203580 [41].…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…This activity is likely to correspond to a caldesmon kinase activity observed in G 0 /G 1 transition (Watson et al, 1993). Indeed, a recent report has shown a rapid increase in MAPK-dependent phosphorylation of caldesmon upon serum stimulation of cultured smooth muscle cells (D'Angelo et al, 1999). Because the sites of MAPK phosphorylation are a subset of the cdc2 kinase sites (Childs et al, 1992;Adam and Hathaway, 1993;Redwood et al, 1993), such phosphorylation would inhibit, to a certain extent, the activities of wild-type caldesmon, however the mutant caldesmon would not be affected.…”
Section: Discussionmentioning
confidence: 99%
“…159,160 Phosphorylation of CaD was also detected in cultured smooth muscle cells upon serum stimulation. 161 Such phosphorylation was markedly reduced by the MEK inhibitor PD98059, but not by the p38 MAPK inhibitor SB203580, 161 thus strongly pointing to ERK-induced phosphorylation during cell proliferation. With the use of mass spectrometry it was shown that phosphorylation at Ser759 and Ser789 of mammalian smooth muscle CaD (or Ser497 and Ser527 in nonmuscle CaD; Fig.…”
Section: Phosphorylation As a Regulatory Mechanismmentioning
confidence: 99%